Comparing the Respiratory Compensation Point With Muscle Oxygen Saturation in Locomotor and Non-locomotor Muscles Using Wearable NIRS Spectroscopy During Whole-Body Exercise - Yogev, Assaf; Arnold, Jem; Clarke, Dave; Guenette, Jordan A.; Sporer, Ben C.; Koehle, Michael S. (Frontiers in Physiology, 2022)
The relationship between the muscle deoxygenation breakpoint (Deoxy-BP) measured with near-infrared spectrometry (NIRS), and the respiratory compensation point (RCP) has been well established. This relationship has also been reported using wearable NIRS, however not in locomotor and non-locomotor muscles simultaneously during whole body cycling exercise. Our aim was to measure muscle oxygen saturation (SmO2) using wearable NIRS sensors, and to compare the Deoxy-BPs at each muscle with RCP during a ramp cycling exercise test. Twenty-two trained female and male cyclists completed a ramp exercise test to task intolerance on a cycling ergometer, at a ramp rate of one watt every two seconds (30 W/min). SmO2 was recorded at the subjects’ right vastus lateralis (VL) and right lateral deltoid. SmO2, and the Deoxy-BPs were assessed using a piecewise double-linear regression model. Ventilation (V̇E) and gas exchange were recorded, and RCP was determined from V̇E and gas exchange using a V-slope method, and confirmed by two physiologists. The SmO2 profiles of both muscles and gas exchange responses are reported as V̇O2, power output (W), and time of occurrence (TO). SmO2 profiles at both muscles displayed a near-plateau or breakpoint response near the RCP. No differences were detected between the mean RCP and mean Deoxy-BP from either the locomotor or non-locomotor muscles, however a high degree of individual variability was observed in the timing and order of occurrence of the specific breakpoints. These findings add insight into the relationships between ventilatory, locomotor, and non-locomotor muscle physiological breakpoints. While identifying a similar relationship between these breakpoints, individual variability was high, hence caution is advised when using wearable NIRS to estimate RCP in an incremental ramp test.